Analisis Persepsi Pelanggan terhadap Kualitas Produk Makanan dan Minuman di Bleusky Resto Semarang - Diva Tiara Anindita; Sita Nurmasitah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to describe customer perceptions of the quality of food and beverage products at Bleusky Resto Semarang. The study used a descriptive quantitative approach involving 33 customers as respondents. Data were collected through a Likert scale questionnaire and analyzed using percentages. The results showed that customer perceptions of food products tended to be positive, indicated by responses of agreeing and strongly agreeing on aspects of breakfast menu variety of 78.80%, variety of cuisines 84.90%, availability of main dishes and snacks 84.80%, presentation of food in fresh and warm conditions 84.90%, and availability of fruits 91.00%. In beverage products, positive perceptions were seen in aspects of breakfast drink variety of 84.90%, availability of hot and cold drinks 87.90%, availability of healthy drinks such as juice and herbal medicine 81.90%, satisfaction enjoying breakfast 81.80%, and interest in diverse beverage choices 81.80%. However, several aspects received lower positive responses, namely coffee variety (63.70%), juice selection (66.70%), and the use of fresh fruit in juices (57.50%). These findings reinforce the understanding that customer perceptions can be used as a basis for evaluating product quality in restaurant businesses and serve as a reference for culinary practitioners and culinary arts researchers in developing food and beverage products that meet consumer expectations.